A non-replicative role of the 3′ terminal sequence of the Dengue virus genome in membranous replication organelle formation - Cerikan, Berati; Göllner, Sarah; Neufeldt, Christopher; Haselmann, Uta; Mulder, Klaas; Chatel-Chaix, Laurent; Cortese, Mirko; Bartenschlager, Ralf (Cell reports, 2020)
Dengue virus (DENV) and Zika virus (ZIKV), members of the Flavivirus genus, rearrange endoplasmic reticulum membranes to induce invaginations known as vesicle packets (VPs), which are the assumed sites for viral RNA replication. Mechanistic information on VP biogenesis has so far been difficult to attain due to the necessity of studying their formation under conditions of viral replication, where perturbations reducing replication will inevitably impact VP formation. Here, we report a replication-independent expression system, designated pIRO (plasmid-induced replication organelle formation) that induces bona fide DENV and ZIKV VPs that are morphologically indistinguishable from those in infected cells. Using this system, we demonstrate that sequences in the 3′ terminal RNA region of the DENV, but not the ZIKV genome, contribute to VP formation in a non-replicative manner. These results validate the pIRO system that opens avenues for mechanistically dissecting virus replication from membrane reorganization.
Gesehen am 13.08.2020